2012
DOI: 10.1007/s00705-012-1316-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and analysis of the complete genome of Rana grylio virus (RGV)

Abstract: Infection with Rana grylio virus (RGV), an iridovirus isolated in China in 1995, resulted in a high mortality rate in frogs. The complete genome sequence of RGV was determined and analyzed. The genomic DNA was 105,791 bp long, with 106 open reading frames (ORFs). Dot plot analysis showed that the gene order of RGV shared colinearity with three completely sequenced ranaviruses. A phylogenetic tree was constructed based on concatenated sequences of iridovirus 26 core-gene-encoded proteins, and the result showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…These ORFs were placed into specific gene groups based on the genomic analysis of Eaton et al (2007), which identified orthologous genes throughout the family using a combination of BLAST searches and Viral Orthologous Clusters software (Eaton et al, 2007). Genes from viral genomes not analysed by Eaton et al (2007) were identified via BLAST searches and analyses conducted by the authors of the published genome sequences (Huang et al, 2009;Jancovich et al, 2010;Lei et al, 2012;Mavian et al, 2012a, b). The first group, the core gene group, included 26 ORFs that have orthologues in all members of the family Iridovirdae (including the two invertebrate genera Iridovirus and Chlorididovirus).…”
Section: Methodsmentioning
confidence: 99%
“…These ORFs were placed into specific gene groups based on the genomic analysis of Eaton et al (2007), which identified orthologous genes throughout the family using a combination of BLAST searches and Viral Orthologous Clusters software (Eaton et al, 2007). Genes from viral genomes not analysed by Eaton et al (2007) were identified via BLAST searches and analyses conducted by the authors of the published genome sequences (Huang et al, 2009;Jancovich et al, 2010;Lei et al, 2012;Mavian et al, 2012a, b). The first group, the core gene group, included 26 ORFs that have orthologues in all members of the family Iridovirdae (including the two invertebrate genera Iridovirus and Chlorididovirus).…”
Section: Methodsmentioning
confidence: 99%
“…RGV, a ranavirus isolated from China, causes systemic hemorrhagic disease with a high mortality rate in frogs. It is also a model system for molecular characterization of ranaviruses [38][39][40][41][42][43]. (v) Ambystoma tigrinum virus is a lethal ranavirus originally isolated from Sonora tiger salamanders in southern Arizona, USA [44,45].…”
Section: Ranaviruses and Their Genomesmentioning
confidence: 99%
“…As a common fish pathogen involved in hemorrhagic disease, Grass carp reovirus (GCRV) not only infects grass carp (Ctenopharyngodon idellus), but also is capable of infecting black carp (Mylopharyngodon piceus), topmouth gudeon (Pseudorasbora parva) and rare minnow (Gobiocypris rarus), causing significant economic losses in freshwater fish aquaculture in China and East Asia (Qiu et al, 2001;Zhang et al, 2003;Pei et al, 2014). Iridoviruses are nucleo-cytoplasmic large DNA viruses and have been recognized as serious pathogens of economically important cold-blooded vertebrates Lei et al, 2012c). Rana grylio virus (RGV), an iridovirus isolated in China in 1995, resulted in a high mortality rate in frogs giant salamanders (Andrias davidianus) is a result of iridovirus infection.…”
Section: Introductionmentioning
confidence: 99%